1989
DOI: 10.1017/s0950268800030697
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent outbreaks of influenza and parvovirus B19 in a boys' boarding school

Abstract: SUMMARYIn the spring term of 1985 there was a protracted outbreak of upper respiratory tract febrile illness consistent with a clinical diagnosis of influenza in a boys' boarding school, which lasted from 23 January to 29 March. Although influenza virus infection was confirmed in 89 % of cases in the first half of the term, 53 % of the cases which occurred in the second half of the term had no evidence of infection with influenza virus. Between 5 February and 31 March 28 boys presented with skin rashes consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1992
1992
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The proportion of the women that demonstrated IgM antibodies (p > 0.05) and IgG antibodies (p < 0.05) increased with the number of children in a household. A previous report claims that children are the main sources of transmission and outbreaks can persist for months in schools and day care centres due to the relatively large number of seronegative children that come in close contact with children within this environment (Grilli et al 1989). Another study reported that the infection is commonly passed through respiratory tract secretions from close personal contact (Corcoran & Doyle 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of the women that demonstrated IgM antibodies (p > 0.05) and IgG antibodies (p < 0.05) increased with the number of children in a household. A previous report claims that children are the main sources of transmission and outbreaks can persist for months in schools and day care centres due to the relatively large number of seronegative children that come in close contact with children within this environment (Grilli et al 1989). Another study reported that the infection is commonly passed through respiratory tract secretions from close personal contact (Corcoran & Doyle 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Corcoran and S. Doyle .70 % of the adult population is seropositive (Kerr et al, 1999). Children are the main source of transmission and outbreaks can persist for months in schools and day-care centres, due to the relatively large number of seronegative children and close contact of children within this environment (Tuckerman et al, 1986;Grilli et al, 1989). The annual seroconversion rate among women of childbearing age has been estimated to be 1 .…”
Section: Infectivity Transmission and Epidemiologymentioning
confidence: 99%
“…B19 outbreaks can persist for months in schools as seronegative children represent a significant reservoir for B19 infection. Recently infected children therefore are the main source of transmission in day-care centres due to the relatively large number of seronegative children and the close contact of children within this environment (Tuckerman et al, 1986;Grilli et al, 1989). The annual seroconversion rate among women of childbearing age has been estimated to be 1.5% during endemic periods and 13% during epidemics (Koch and Adler, 1989;Valeur-Jensen et al, 1999).…”
Section: General Clinical Features and Chronic Infectionmentioning
confidence: 99%